UMP award shows R&D focus success - Hidir, Reduan (The New Straits Times Press (M) Bhd., 2017)
UNIVERSITI Malaysia Pahang's (UMP) success in securing the National Innovation Award for Product Category at the 2017 National Innovation and Creative Economy Expo (Nice) on Friday is testament to the university's impact in research and development (R&D).